Meningkatkan Hasil Belajar Melalui PBL Bagi Peserta Didik Kelas VIII SMP Negeri 1 Onan Ganjang - Roita Pandiangan; Alfonsus Mudi Aran; Aserie M.M. Dungus (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of class VIII students of SMP Negeri 1 Onan ganjang in the subjects of canonical religions education and Character education through the application of the Problem based Learning (Pbl) Learning model.This method was chosen as a solution to the low interest and learning outcomes of students, especially in understanding the material of the Church as a Sign and means of salvation.This study uses a Classroom action Research(CAR)approach which is carried out in two cycle includes the stages of planding, Implementing actions, Observation, and reflection. The results of the study showed that the application of the PBL learning Model Succeeded in improving student learning outcomes in the cognivite, Affective, and pocomotor aspects.in the 1-mile cycle, the average student test results reached 76, Which increased to 85 in cycle II.In addition, student participation in group discussions increased significantly as seen from the results of Observations that showed an increse in students ability to solve problems, provide alternative solutions, and appreciate other people’s points of view. In conclusion, the application of the problem Based Learning (PBL) Learning model has proven effective in improving student learning outcome, both in rearms of knowledge and social skills. The applications of this model not only improves students active participation and learning motivation. It is recommended for teachers to continue applying this medhod in learning.